Modified Boron Nitride Powder
The modified boron nitride powder, produced via frictional treatment under inert gas conditions, addresses the limitations of existing powders by improving adhesion and spreadability, resulting in a uniform cosmetic application.
Patent Information
- Application Number
- JP2021542812
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-08-28
- Filing Date
- 2020-08-20
- Publication Date
- 2025-01-31
- Estimated Expiration
- 2040-08-20
AI Technical Summary
Existing boron nitride powders used in cosmetics have limitations in terms of exhibition and adhesion due to particle shape and impurities, leading to uneven application and poor adherence to the skin.
A modified boron nitride powder is produced through a frictional treatment using a rotating drum with boron silicate glass under inert gas conditions, which alters the particle's electrical properties from negative to positive, reducing lumps and enhancing fluidity, resulting in improved adhesion and spreadability.
The modified boron nitride powder exhibits enhanced adhesion and spreadability, providing a uniform and fluffy texture when applied to the skin, suitable for cosmetic applications.
Smart Images

Figure 0007624925000001 
Figure 0007624925000002 
Figure 0007624925000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a modified boron nitride powder whose properties have been modified to make it suitable for use as a cosmetic material, and further relates to a method for modifying the same. [Background technology]
[0002] Boron nitride powder is a white extender pigment having a hexagonal layered crystal structure, and is widely used as a powder base material in cosmetics such as make-up cosmetics for the purposes of imparting gloss, improving feel, increasing volume, etc.
[0003] Incidentally, cosmetics are required to have covering power, transparency, spreadability, lubricity, adhesion to human skin, etc., and boron nitride powder is known to have properties that impart spreadability and adhesion in particular, and in order to further improve such properties, attention has been paid to the particle shape of the primary particles, such as the particle size (major axis), thickness, aspect ratio, etc. For example, Patent Document 1 reports that boron nitride powder consisting of primary particles with an average major axis of 5 to 8 μm, an average thickness of 0.25 to 0.5 μm, and an average aspect ratio (major axis / thickness) of 15 to 20 is excellent in the effect of imparting spreadability and adhesion. However, there is a limit to how much the ductility and adhesiveness of boron nitride powder can be improved simply by adjusting the shape of the primary particles.
[0004] In addition, Patent Document 2 describes a graphitization index (GI) of 2.0 or less and a specific surface area of 15 m 2 It is disclosed that hexagonal boron nitride powder having a molecular weight of 1.0 μm or less is washed and dried with an acid solution of 0.02 to 0.5 chemical equivalents per mole of hexagonal boron nitride, and then the washed and dried powder is kept in a sealed container so as not to come into contact with carbon, and heat-treated at 1800 to 1950°C for 1 to 5 hours in a nitrogen atmosphere to modify the boron nitride powder. With this method, for example, the whiteness index is improved to 95.0 or more, but the spreadability and adhesion required for cosmetic applications are insufficient. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6109466 [Patent Document 2] JP 2004-35273 A Summary of the Invention [Problem to be solved by the invention]
[0006] An object of the present invention is to provide a modified boron nitride powder that can greatly improve the properties required when incorporated into cosmetics, such as spreadability and adhesion. Another object of the present invention is to provide a modification method for obtaining the above modified boron nitride powder. [Means for solving the problem]
[0007] The inventors of the present invention believed that conventional boron nitride powder contains many lumps (large aggregates that can be seen with the naked eye), and tends to become uneven when applied to the hands or a cosmetic sponge, which is the reason for insufficient spreadability and adhesion when used in cosmetics. Based on this belief, the inventors conducted many experiments and discovered the novel finding that boron nitride powder containing many lumps exhibits negative charging when subjected to a triboelectric test using a rotating drum made of anodized aluminum and equipped with a boron silicate glass window, and that by heat treating this powder under specific conditions, this triboelectric charging property can be modified to positive charging and the number of lumps can be reduced, and the present invention was completed based on this finding.
[0008] According to the present invention, the voltage density measured by the triboelectric charging test is +10V / g or more and +59V / g or less, and whiteness (L value) is 90.0 or more and a b value in the Lab color system is 4 or more and 14.1 or less.
[0009] In the modified boron nitride powder of the present invention, (1 ) Avalanche energy is 40mJ / kg or less, ( 2) the average major axis of the primary particles is in the range of 2 to 20 μm, the average thickness is in the range of 0.2 to 2.0 μm, and the average aspect ratio is in the range of 5 to 20; ( 3 ) To be used as a cosmetic compounding agent; is preferred.
[0010] According to the present invention, further, a negatively triboelectrically charged boron nitride powder (hereinafter, sometimes simply referred to as negatively charged boron nitride powder) is subjected to a triboelectric charging test at a temperature of 1700 to 2200° C. under a rare gas flow, and the voltage density is measured. +10V / g or more +59V / g or less, whiteness (L value) is 90.0 or more The present invention provides a method for modifying boron nitride powder, which comprises heat-treating the powder until the b value in the Lab color system is 44 or more and 14.1 or less.
[0011] In the modification method of the present invention, (1 ) heat treating the negatively charged boron nitride powder while flowing it under a flow of inert gas; is preferred.
[0012] In the present invention, the triboelectric charging test is carried out using a rotating drum (drum capacity: 332 cc) made of anodized aluminum equipped with a boron silicate glass window, and as described in the examples below, the test is carried out by placing a sample powder in the rotating drum and rotating the drum at a speed of 10 rpm for 300 seconds to triboelectrically charge the sample powder (see the examples for detailed conditions). Therefore, in the present invention, the chargeability of boron nitride powder means the triboelectric chargeability measured using the above-mentioned rotating drum type powder flowability measuring device. The above-mentioned avalanche energy is also measured by carrying out a powder flowability test using the above-mentioned powder flowability measuring device. Effect of the Invention
[0013] The modified boron nitride powder of the present invention has the property of being positively charged when subjected to the above-mentioned triboelectric charging test. Conventional boron nitride powder is negatively charged when subjected to such a triboelectric charging test. In other words, the modified boron nitride powder of the present invention, due to its positive charging property, has very few lumps and is a powder that has a fluffy feel (i.e., a lightweight feel). Therefore, when the modified boron nitride powder of the present invention is used in cosmetics, such as powder foundation, the spreadability and adhesion are greatly improved, and when applied to the skin, it can be adhered evenly and without unevenness to the skin surface with a single rubbing action.
[0014] In the present invention, in order to obtain the modified boron nitride powder that is triboelectrically charged to a positive polarity as described above, it is necessary to heat treat a conventionally known boron nitride powder (i.e., a boron nitride powder that is triboelectrically charged to a negative polarity) at a temperature of 1300 to 2200°C under a flow of inert gas. That is, various methods are known for producing boron nitride powder, but the powder produced by any method contains extremely small amounts of functional groups such as OH groups and CN groups, as well as B groups, on the surfaces of the particles that make up the powder. 2 O 3 Impurities such as these are present. When boron nitride powder consisting of particles with such functional groups and impurities present on the surface is frictionally charged using a rotating drum made of a specified material, it becomes negatively charged. However, in the present invention, these functional groups and impurities are removed by the above-mentioned heat treatment, and as a result, the heat-treated boron nitride powder (modified boron nitride powder) exhibits positive charging properties.
[0015] For example, in the above-mentioned Patent Document 2, the boron nitride powder is heat-treated, but this heat treatment is performed in a closed container and in a nitrogen atmosphere. That is, in the present invention, the heat treatment is performed under so-called dynamic conditions while flowing an inert gas, so that the negatively chargeable substance (hereinafter, sometimes simply referred to as negatively chargeable substance) present on the particle surface is removed, but in the case of the heat treatment performed under static conditions where the nitrogen gas is not flowed but only in a nitrogen gas atmosphere as in Patent Document 2, the negatively chargeable substance on the particle surface is not removed, and therefore, positively chargeable boron nitride powder is not obtained. In fact, as shown in the examples described later, in Examples 1 to 11 where the heat treatment is performed under dynamic conditions while flowing an inert gas (nitrogen gas or Ar gas), a voltage density of +11 V / g or more is obtained, but in Comparative Example 3 where the heat treatment is merely performed under static conditions in a nitrogen atmosphere without flowing nitrogen gas, the voltage density is -6 V / g, and positively chargeable boron nitride powder is not obtained.
[0016] In addition, when producing boron nitride by reduction nitridation, for example, a boron source compound is heated to a temperature of about 1300 to 1550°C while flowing nitrogen gas in a nitriding furnace to perform reduction nitridation, generating amorphous boron nitride, which is then heat-treated at about 1700 to 2200°C, which promotes crystallization and produces crystallized boron nitride powder. In this case, reduction nitridation and the subsequent heat treatment (crystallization) are performed in the same nitriding furnace, so that the heat treatment is also performed in this case as in the present invention. However, the boron nitride powder obtained in this case is positively triboelectrically charged, and boron nitride powder with suppressed agglomeration cannot be obtained. It is likely that at this stage, there are alkaline substances or B in the boron nitride powder. 2 O 3 It is believed that this is because the alloy contains a large amount of impurities such as those listed above, and that the impurities cannot be removed by heat treatment in the presence of nitrogen gas (inert gas). Incidentally, in the present invention, the heat treatment (modification treatment) for changing the triboelectric charge from negative to positive is carried out after the boron nitride is crystallized and at least after acid washing and water washing are carried out. This removes most (but not all) of the above-mentioned impurities that cause negative charging, and the above-mentioned heat treatment under an inert gas flow removes trace amounts of the above-mentioned impurities, resulting in boron nitride powder with positive triboelectric charge and reduced clumping. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] <Modified boron nitride powder> The modified boron nitride powder of the present invention is composed of hexagonal boron nitride particles, and when a frictional charging test is performed using a rotating drum type powder flowability measuring device (see Examples for detailed conditions), the voltage density (charge amount) is +1 V / g or more, preferably +10 V / g or more, and more preferably +30 V / g or more. The higher the voltage density, the less the particles aggregate, resulting in a fluffy boron nitride powder with almost no lumps, and when blended in a cosmetic, the spreadability and adhesion are good. If the voltage density is less than 1 V / g (or negatively charged), the particles tend to aggregate and form lumps, and as a result, the spreadability and adhesion of the cosmetic cannot be improved. Although there is no particular upper limit for the voltage density, if the particles are excessively easily positively charged, handling becomes difficult, so the voltage density is preferably +200 V / g or less, more preferably +100 V / g or less. That is, the heat treatment during the modification described below is carried out until the charge density falls within the above range.
[0018] The modified boron nitride powder of the present invention has excellent fluidity due to the positive triboelectric charging property as described above. This fluidity can be expressed by avalanche energy (change in potential energy before and after avalanche) which indicates powder fluidity. That is, the avalanche energy is measured using a rotating drum type powder fluidity measuring device like the voltage density described above (see Examples for detailed conditions), and the lower this value, the better the fluidity and the better the spreadability and adhesion can be obtained. For example, in the modified boron nitride powder of the present invention, this avalanche energy is in the range of 40 mJ / kg or less, preferably 35 mJ / kg or less, more preferably 30 mJ / kg or less. In addition, although there is no lower limit to the preferred range of this avalanche energy, it is usually 10 mJ / kg or more.
[0019] The modified boron nitride powder of the present invention is not particularly limited in terms of properties other than the charge density and the flowability based on the charge density, but it is desirable for the powder to have the properties conventionally required for cosmetic applications.
[0020] For example, the primary particles of this modified boron nitride powder preferably have an average major axis of 2 to 20 μm, particularly 3 to 10 μm, an average thickness of 0.2 to 2.0 μm, particularly 0.3 to 1.0 μm, and an average aspect ratio (average major axis / average thickness) of 5 to 20, particularly 6 to 18. In addition, the median diameter (D1: volume-based median diameter D 50 The median diameter (D2) of the powder measured by a laser diffraction / scattering method in a state where the powder is ultrasonically dispersed in ethanol is preferably 4 to 14 μm.
[0021] The amount of eluted boron in the modified boron nitride powder of the present invention is preferably 20 ppm or less. This amount of eluted boron is measured by a method specified in the Quasi-Drug Raw Materials Standards 2006. The Quasi-Drug Raw Materials Standards 2006 stipulates that the amount of eluted boron must be 20 ppm or less from the viewpoints of safety and hygiene.
[0022] Furthermore, the modified boron nitride powder of the present invention generally has a whiteness (L value) of 90.0 or more, a redness (a value) of -3.0 to 0, and a yellowness (b value) in the range of 0 to 15.0, as expressed in the Lab color system.
[0023] The modified boron nitride powder of the present invention described above has almost no lumps, and therefore has a low bulk density. The bulk density also varies greatly depending on the average major axis and average thickness. For example, a powder with an average major axis of 4 μm and an average thickness of 0.6 μm has a loose bulk density of 0.11 g / cm. 3 Below, tap bulk density 0.33g / cm 3 If the average major axis is 9 μm or less and the average thickness is about 1 μm, the bulk density is 0.2 g / cm 3 Below, tap bulk density 0.6g / cm 3 The following is the result.
[0024] Furthermore, a fluidization test using a rotating drum type powder fluidity measuring device used for measuring charge density and friction avalanche energy shows that the modified boron nitride powder of the present invention is a powder with few lumps and a fluffy feel. That is, in a fluidization test performed by rotating a standard rotating drum containing 100 cc of sample powder at high speed (see Examples for detailed conditions), when the height of the lower part of the powder layer in the drum is measured, the height of this powder layer of the modified boron nitride powder of the present invention is 2.2 cm or more when the drum rotation speed is 20 rpm, and 2.8 cm or more when the drum rotation speed is 50 rpm. The larger this value, the fewer lumps and the fluffier the powder is.
[0025] The basic fluidity energy in dynamic fluidity tests is known as a parameter indicating that a powder contains almost no agglomerates and has a fluffy feel. As shown in the examples described below, this basic fluidity energy is indicated by the torque applied to the rotor when a rotor is inserted into a 160 mL split container filled with a sample powder using a powder rheometer (e.g., Malvern FT-4). The lower this basic fluidity energy (torque applied to the rotor), the less lumps there are and the more fluffy the powder is. The boron nitride powder of the present invention has the above-mentioned basic fluidity energy of 100 mJ or less, and from this value it can be understood that the powder contains few lumps (aggregates) and has a fluffy feel.
[0026] <Production of boron nitride powder> In the present invention, the boron nitride powder to be subjected to the modification treatment can be produced by various methods known per se, and for example, the melamine method and the reduction nitridation method are known as representative production methods. As already explained, in any of these production methods, the obtained powder has functional groups such as OH and CN and B on the surface of the particles constituting the powder. 2 O 3 These impurities cannot be completely removed by acid washing or the like, and when the resulting powder is subjected to frictional electrification under specified conditions, it becomes negatively charged.
[0027] For example, the melamine method involves reacting boric acid and melamine at a temperature of about 1000°C to obtain low-crystalline boron nitride powder, heating this powder at a temperature of about 1700 to 2200°C to highly crystallize the boron nitride powder, and then washing away by-products other than boron nitride that are present in the reaction product. The reduction-nitridation method is a method in which an oxygen-containing boron compound, a carbon source and an oxygen-containing alkaline earth metal compound are reduced and nitrided by heating in a nitrogen atmosphere to obtain amorphous boron nitride, which is then crystallized by heating at a high temperature to obtain hexagonal boron nitride powder, and by-products other than boron nitride present in the reaction product are then removed by acid washing.
[0028] In the present invention, boron nitride powder may be produced by any method, but the melamine method requires a long heating step and often requires intermediate or post-treatment steps such as crushing, pulverization, and classification, resulting in high production costs. In contrast, the reduction-nitridation method requires a short heating step and requires fewer intermediate and post-treatment steps, thereby reducing production costs. In addition, boron nitride powder obtained by the reduction-nitridation method inherently has few strong agglomerations of primary particles and has a uniform particle size, so the burden of crushing, pulverization, classification, etc. is small, which is advantageous in obtaining a primary particle shape suitable for use in cosmetics, and further has the advantage of a significant modification effect by heat treatment, which will be described in detail later. Therefore, the reduction-nitridation method is preferably adopted in the present invention.
[0029] <Production of boron nitride powder by reduction-nitridation method> A method for producing boron nitride powder by reduction nitridation will be described below. In this method, as described above, an oxygen-containing boron compound, a carbon source, and an oxygen-containing alkaline earth metal compound are used as raw materials, these raw materials are mixed, the raw material mixture is reacted in a nitrogen atmosphere (reduction-nitridation), and then by-products and impurities are removed.
[0030] Oxygenated boron compounds; The oxygen-containing boron compound used as the boron source is not particularly limited, and examples thereof include boric acid, boric anhydride, metaboric acid, perboric acid, hypoboric acid, sodium tetraborate, sodium perborate, etc. In general, boric acid, which is easily available, is preferably used.
[0031] Carbon source; The carbon source is not particularly limited, but examples thereof include amorphous carbon such as carbon black, activated carbon, and carbon fiber, crystalline carbon such as diamond, graphite, and nanocarbon, and pyrolytic carbon obtained by pyrolyzing a monomer or polymer, etc. Generally, inexpensive carbon black is used.
[0032] This carbon source functions as a reducing agent for the oxygen-containing boron compound. Increasing the amount of carbon source added increases the yield of boron nitride powder, but adding too much carbon leaves carbon as an impurity. Conversely, decreasing the amount of carbon source added decreases the yield of boron nitride powder. The amount of carbon source added is not particularly limited, but the ratio of the oxygen-containing boron compound to the carbon source is preferably set so that B / C (element ratio) is 0.5 to 1.0.
[0033] Oxygen-containing alkaline earth metal compounds; The oxygen-containing alkaline earth metal compound functions as a crystallization catalyst. Such oxygen-containing alkaline earth metal compound is not particularly limited, but for example, magnesium oxide, calcium oxide, magnesium carbonate, calcium carbonate, magnesium hydrogen carbonate, calcium hydrogen carbonate, magnesium hydroxide, calcium hydroxide, magnesium nitrate, calcium nitrate, magnesium sulfate, calcium sulfate, magnesium phosphate, calcium phosphate, magnesium oxalate, calcium oxalate, etc. can be used, and two or more of these can be mixed and used.
[0034] Increasing the amount of oxygen-containing alkaline earth metal compound added increases the particle size of the resulting boron nitride particles, whereas decreasing the amount of added boron nitride particles decreases the particle size of the resulting boron nitride particles. Therefore, the particle size of the desired boron nitride particles can be adjusted by adjusting the amount of added oxygen-containing alkaline earth metal compound. From the viewpoint of obtaining boron nitride powder in the primary particle form described above, the amount of oxygen-containing alkaline earth metal compound (MO; M is an alkaline earth metal) and the amount of oxygen-containing boron compound (B 2 O 3 ) and the molar ratio (MO / B 2 O 3 ) should be added in the range of 0.01 to 1.00.
[0035] Raw material mixing; The method for mixing the above raw materials (oxygen-containing boron compound, carbon source, and oxygen-containing alkaline earth metal compound) is not particularly limited, and the mixture can be mixed using a general mixer such as a vibration mill, a bead mill, a ball mill, a Henschel mixer, a drum mixer, a vibration agitator, or a V-shaped mixer.
[0036] reduction nitridation; The reduction-nitridation of the raw material mixture is carried out by supplying the raw material mixture into a nitriding furnace and heating it in a nitrogen atmosphere, whereby the boron-containing compound is reduced and nitrided to obtain boron nitride. This reaction proceeds at temperatures above 1200°C and is represented by the following formula: B 2 O 3 +3C+N 2 →2BN+3CO
[0037] Amorphous boron nitride is obtained by this reduction-nitridation, and this can be crystallized by heating at high temperatures, for example at 1700° C. or higher, to obtain hexagonal boron nitride powder.
[0038] Therefore, the above reduction-nitridation reaction is carried out by heating to a temperature of 1200°C or higher, particularly 1300°C or higher, and heating is continued even after boron nitride is produced, and crystallization is carried out by heating at a high temperature of 1700°C or higher. During such heating, it is important to control the amount of carbon in the reaction product. Specifically, it is preferable to allow the reaction to proceed in a nitrogen atmosphere so that the carbon concentration is 5 mass% or less before the temperature reaches 1550°C. If more than 5 mass% carbon remains, CaB 6 The carbon concentration in the reaction mixture can be controlled using an X-ray fluorescence analyzer, and from an industrial perspective, it is sufficient if the carbon concentration is reduced to about 1% by mass.
[0039] The method for confirming whether the carbon concentration in the reactants satisfies the range of 5 mass% or less before the temperature reaches 1550°C is not particularly limited. For example, the carbon concentration in the reactants can be directly controlled by measuring the carbon concentration in the reactants at a temperature of 1550°C, but it is industrially preferable to carry out an experiment in advance, identify the time at which the carbon concentration in the reactants becomes 5 mass% or less under the operating conditions of the nitriding furnace including the temperature profile, and control the treatment time according to this operating condition. The treatment time varies depending on the operating conditions and cannot be determined in general, but is generally in the range of 2 to 10 hours, particularly 3 to 8 hours, at a temperature of 1200°C or more.
[0040] Crystallization; Heating is continued even after the above reduction nitridation, and the amorphous boron nitride is crystallized by heat treatment at 1700° C. or higher, particularly at 1700 to 2200° C., to obtain hexagonal boron nitride powder.
[0041] The temperature and holding time of this heat treatment can be appropriately adjusted depending on the particle size of the desired boron nitride particles, and a lower temperature and a shorter heat treatment time tend to produce boron nitride particles with smaller particle sizes, while a higher temperature and a longer heat treatment time tend to produce boron nitride particles with larger particle sizes. The heat treatment time is usually 0.5 to 6 hours, preferably 1 to 4 hours.
[0042] The nitrogen atmosphere in the nitriding furnace can be formed by a known means. The gas introduced into the nitriding furnace is not particularly limited as long as it is a gas that can give nitrogen to boron under the above nitriding treatment conditions, and nitrogen gas and ammonia gas can be used, and a gas in which a non-oxidizing gas such as hydrogen, argon, or helium is mixed with nitrogen gas or ammonia gas can also be used.
[0043] As the nitriding furnace, any known furnace capable of controlling the reaction atmosphere can be used, such as an atmosphere-controlled high-temperature furnace in which heat treatment is performed by high-frequency induction heating or heater heating. In addition to batch furnaces, continuous furnaces such as pusher-type tunnel furnaces and vertical reaction furnaces can also be used.
[0044] Acid washing; The hexagonal boron nitride powder obtained as described above contains compounds such as calcium borate as impurities, so washing with an acid can produce a highly pure and highly crystalline hexagonal boron nitride powder. If a large amount of compounds such as calcium borate remains, it is difficult to obtain the effect of the modification treatment by heating described below, and it is difficult to obtain a boron nitride powder with few lumps.
[0045] The method of acid washing is not particularly limited, and a known method can be used. For example, the powder or lumps of impurity-containing boron nitride obtained after nitriding treatment are broken down by hand and put into a container, and dilute hydrochloric acid (10 to 20 mass % HCl) is added in an amount 5 to 10 times the amount of the impurity-containing boron nitride powder, and the mixture is allowed to come into contact for 4 hours or more. As the acid used for acid washing, nitric acid, sulfuric acid, acetic acid, etc. can be used in addition to hydrochloric acid.
[0046] After the acid washing, the powder is washed with pure water in a conventional manner to remove the remaining acid. The method of washing with water is to filter the acid used in the acid washing, disperse the acid-washed boron nitride powder in the same amount of pure water as the acid used, and filter again. Furthermore, washing with pure water and filtration are repeated until the filtrate becomes neutral. After the acid washing and water washing, drying is performed. This drying can be performed by air drying at 50 to 250°C, or by drying under reduced pressure. The drying time is preferably until the moisture content approaches 0%, and generally, it is recommended to perform drying at the above temperature for 1 to 48 hours.
[0047] The boron nitride powder from which impurities have been removed by acid washing and water rinsing as described above is optionally subjected to processes such as pulverization, crushing, and classification by known methods, and then subjected to the next modification process.
[0048] <Modification of boron nitride powder> The boron nitride powder obtained as described above can be made suitable for use in cosmetics in terms of the primary particle shape (e.g., average major axis, average thickness, and aspect ratio) by adjusting the reaction conditions, etc., but the powder has many lumps and a heavy texture. In the present invention, the following modification treatment significantly reduces the lumps and modifies the powder to one with a fluffy (lightweight) texture.
[0049] In the present invention, this modification treatment is carried out by heat treating the boron nitride powder at a temperature of 1300 to 2200° C., and it is important that this heat treatment is carried out in a flow of inert gas.
[0050] That is, the boron nitride powder is placed under a flow of inert gas heated to a predetermined temperature, and the flowing inert gas is brought into contact with the boron nitride powder, thereby carrying out a heat treatment (i.e., a modification treatment).By carrying out such a treatment, a boron nitride powder with few lumps and a fluffy feel can be obtained. In this way, by heat treatment under a flow of inert gas, the functional groups and impurities present in small amounts on the surface of the particles that make up the powder are thermally decomposed and the thermal decomposition products are removed, changing the triboelectric charging properties, so that the voltage density in a triboelectric charging test under specified conditions becomes +1V / g or more, the avalanche energy becomes 40mJ / kg or less, clumping is suppressed, and a modified boron nitride powder with a fluffy feel is obtained.
[0051] In the above-mentioned modification treatment (heat treatment), the inert gas is typically a rare gas such as helium, neon, or argon, but nitrogen can also be used, and from the viewpoint of economy, nitrogen is preferred. A mixture of these gases can also be used.
[0052] The conditions for flowing the inert gas are not particularly limited as long as they are such that the gas present near the surface of the boron nitride powder can be diffused and a part of the gas can be exhausted. For example, a flowing mode in which the inert gas is supplied onto the layer of boron nitride powder and then exhausted, or a flowing mode in which the inert gas is replaced (supplied and exhausted) by a part of the inert gas while the boron nitride powder is fluidized (so-called a fluidized bed mode) can be adopted. Among these, fluidizing the boron nitride powder is preferable in terms of efficient modification.
[0053] Furthermore, the flow rate of the inert gas varies depending on the mode of the heat treatment, the treatment temperature, the internal structure of the apparatus, etc., and cannot be determined in general, but is suitably 0.02 to 5 L (volume at 25° C.) / min per 1 L of the volume of the boron nitride powder to be treated. In a mode in which the boron nitride powder is fluidized using a fluidized bed for treatment, sufficient treatment is possible even with a reduced flow rate of the inert gas, and specifically, treatment is possible at 0.02 to 0.5 L (volume at 25° C.) / min, particularly 0.05 to 0.3 L (volume at 25° C.) / min per 1 L of the volume of the boron nitride powder to be treated.
[0054] The temperature of the heat treatment is 1300 to 2200°C as mentioned above, but if the temperature is too low, the effect of reducing lumps is not obtained sufficiently, and the treatment takes a long time, and if the temperature is too high, the thermal energy and equipment costs are high, which is economically disadvantageous. Therefore, the heating temperature is preferably 1400 to 2000°C, more preferably 1500 to 1950°C. Furthermore, the heating retention time varies depending on the inert gas treatment conditions and heating temperature, but it is sufficient to set it so that the voltage density (frictional electrification amount) of the powder is +1V / g or more, preferably +10V / g or more, and more preferably +30V / g or more, and is usually about 0.2 to 20 hours, particularly about 0.5 to 10 hours.
[0055] The above-mentioned reforming treatment can be carried out, like the reduction nitridation described above, using a known device capable of controlling the reaction atmosphere, for example, an atmosphere-controlled high-temperature furnace which performs heat treatment by high-frequency induction heating or heater heating. In addition to a batch furnace, a pusher-type tunnel furnace, a vertical reaction furnace, or other continuous furnace can also be used.
[0056] In addition, the above-mentioned modification process of the present invention can adjust the coloring degree of the powder. That is, when many nitrogen vacancies are generated in boron nitride, the whiteness of boron nitride decreases and the yellowness increases, and a modified boron nitride powder suitable for cosmetics with a color similar to human skin can be obtained. For example, when a rare gas is used as the inert gas, by setting the heating temperature in the range of 1700 to 2200°C, a modified boron nitride powder with a high yellowness (b value) of 4 or more in the Lab color system and a color similar to human skin can be obtained. On the other hand, in order to obtain a modified boron nitride powder with high whiteness, nitrogen gas should be used and the heating temperature should be set to 1300° C. or higher and lower than 2200° C., particularly 1300 to 2000° C., more preferably in the range of 1500 to 2000° C., and optimally 1600° C. or lower. This results in a modified boron nitride powder with high whiteness, in which the whiteness (L value) is 99.0 or higher, the redness (a value) is −0.5 to 0, and the yellowness (b value) is 0 to 2.0 in the Lab color system. The modified boron nitride powder obtained in this manner is suitable for use in cosmetics, and by incorporating it into cosmetics, it is possible to greatly improve the spreadability and adhesion to the skin. EXAMPLES
[0057] The present invention will be described in detail below with reference to examples, but the present invention is not limited to these examples.
[0058] In the following examples and comparative examples, various tests and measurements were carried out by the following methods.
[0059] (1) Average length, average thickness, aspect ratio 10 parts by mass of boron nitride powder was dispersed in 100 parts by mass of epoxy resin (EA E-30CL, manufactured by Henkel), and the resulting resin composition was degassed under reduced pressure and then poured into a 10 mm square, 1 mm thick mold and cured at a temperature of 70°C.
[0060] Next, the cured resin composition was removed from the mold, and both sides were polished so that they were parallel to each other. Furthermore, the center of one of the faces perpendicular to the thickness direction of the resin composition was cross-sectionally milled, and an image of the processed surface was taken using an SEM at a magnification of 2500x. One hundred boron nitride particles were randomly selected from the obtained images, and the long side (= major axis) and short side (= thickness) of the particles were measured taking into account the magnification. The average values were taken as the average long axis (μm) and average thickness (μm), respectively. Furthermore, the aspect ratio (average long axis / average thickness) was calculated from these values.
[0061] (2) Median diameter (D1: μm) 0.3 g of boron nitride powder was added to 50 cc of ethanol, and the boron nitride suspension was measured for particle size distribution using a laser diffraction / scattering particle size distribution analyzer (HORIBA LA-950V2). The volume-based average particle size (D 50 ) was defined as the median diameter (D1).
[0062] (3) Median diameter (D2: μm) 0.3 g of boron nitride powder was placed in a 100 cc, 4 cm diameter screw cap bottle together with 50 cc of ethanol, and ultrasonic waves were applied from a 0.2 cm diameter probe immersed 1 cm into the water at 100 W output for 20 minutes at room temperature. The particle size distribution of the boron nitride suspension was then measured in the same manner as for the median system (D1), and the volume-based average particle size (D 50 ) was defined as the median diameter (D2).
[0063] (4) Whiteness, redness, and yellowness according to the Lab color system The whiteness (L value), redness (a value), and yellowness (b value) were measured using a Nippon Denshoku Industries Co., Ltd. ZE6000. The measurements were carried out in a quartz glass cell measuring 30 mm in diameter and 13 mm in height, filled with boron nitride powder.
[0064] (5) Loose bulk density, tapped bulk density The light bulk density (g / cm) was measured using a Seishin Enterprise Tap Denser KYT-5000. 3 ) and tapped bulk density (g / cm 3 ) was measured. The sample cell was 100 ml, the tapping speed was 120 times / min, the tapping height was 5 cm, and the number of tapping times was 500.
[0065] (6) Amount of dissolved boron The dissolved boron was extracted according to the method specified in the Quasi-Drug Raw Materials Standards 2006, and the amount of boron (ppm) was measured using an ICP atomic emission spectrometer.
[0066] That is, 2.5 g of boron nitride powder was placed in a Teflon beaker, 10 mL of ethanol was added and mixed well, and then 40 mL of water was added and mixed well. A Teflon watch glass was then placed on top and the mixture was heated at 50° C. for 1 hour. After cooling, the mixture was filtered, the residue was washed with a small amount of water, and the washings were mixed with the filtrate. This liquid was further filtered through a membrane filter (0.22 μm). The entire filtrate was placed in a Teflon (registered trademark) beaker, 1 mL of sulfuric acid was added, and the mixture was boiled on a hot plate for 10 minutes. After cooling, the liquid was placed in a polyethylene measuring flask, a Teflon (registered trademark) beaker was washed with a small amount of water, and the mixture was added to the polyethylene measuring flask, followed by adding water to make exactly 50 mL. This was used as a sample solution, and the amount of boron in the sample solution was measured using an ICP atomic emission spectrometer.
[0067] (7) Voltage density (V / g) A frictional electrification test was carried out using a rotating drum type powder flowability measuring device, REVOLUTION manufactured by Mercury Scientific, and the voltage density (V / g) was measured. Specifically, 100 cc of boron nitride powder was placed in a standard rotating drum, and after neutralization with an ionizer, the charge amount (V) was measured while the rotating drum was rotating at 10 rpm for 300 seconds. Since the charge amount (V) fluctuates significantly and is unstable immediately after the rotating drum starts to rotate, the average charge amount (V) during the stable period of 200 to 300 seconds was calculated, and the voltage density (V / g) was determined by dividing the average charge amount (V) by the weight (g) of the boron nitride powder placed in the rotating drum. The above-mentioned standard rotating drum has a cylindrical shape with an inner surface made of anodized aluminum, a boron-silicate glass window is attached to each side of the cylinder, and the drum capacity is 332 cc.
[0068] (8) Avalanche Energy A fluidity test was performed using the powder fluidity measuring device that was also used to measure the charge density, and the avalanche energy (mJ / kg) was measured. Specifically, 100 cc of boron nitride powder was placed in the standard rotating drum described above, and after neutralizing it with an ionizer, the rotating drum was rotated at a rotation speed of 0.3 rpm. The avalanche energy of the avalanche that occurred (the change in potential energy before and after the avalanche) (mJ / kg) was measured, and the average value for 150 avalanches was taken as the avalanche energy (mJ / kg).
[0069] (9) Powder bed height in fluidization test A fluidization test was carried out using the above powder fluidity measuring device, and the height (cm) of the powder layer was measured. Specifically, 100 cc of boron nitride powder was placed in the above-mentioned standard rotating drum, and after neutralizing the powder with an ionizer, the height of the powder layer (height of the lowest point of the powder layer) (cm) was measured when the rotating drum was rotated at a specified rotation speed (20, 50 rpm). This powder layer height (cm) is an index showing how easily the powder can be fluidized, and tends to be larger for powders that are easier to fluidize.
[0070] In the table summarizing the results of the examples, "*" indicates that the voltage density was high, the powder became charged and adhered to the drum wall surface, and thus the measurement could not be performed correctly.
[0071] (10) Basic fluidity energy by dynamic fluidity test A dynamic flow test was carried out using a Malvern powder rheometer FT-4 to measure the basic flow energy (mJ). Specifically, a 160 mL split container with a height of 89 mm was placed on top of a 51 mm high cylinder, and boron nitride powder was placed in an amount exceeding 89 mm in height. Conditioning was performed four times (impeller tip speed 60 mm / sec, approach angle 5°), and then the cylinder placed on top of the split container was slid to wear down the boron nitride powder. Next, the torque (mJ) applied to the rotor was measured while moving from a height of 100 mm to 10 mm from the bottom of the container at a tip speed of 100 mm / sec and an approach angle of -5°, and the torque value was taken as the basic fluidity energy (mJ). The basic fluidity energy (mJ) is an index of the fluidity of a powder, and tends to be smaller for powders with better fluidity.
[0072] <Example 1> A mixture of the following formulation was prepared using a ball mill. Boron oxide 70g Carbon black 30g Calcium carbonate 10g This mixture was placed in a graphite Tammann furnace and heated to 1500°C at a rate of 15°C / min under a nitrogen gas atmosphere, and held at 1500°C for 6 hours to carry out a reduction-nitridation treatment. Subsequently, the mixture was heated to 1800°C at a rate of 15°C / min and held at 1800°C for 2 hours to carry out a crystallization treatment, thereby obtaining crude hexagonal boron nitride powder.
[0073] The resulting crude hexagonal boron nitride powder was then placed in a polyethylene container, and an aqueous hydrochloric acid solution (10% by mass HCl) in an amount 10 times the amount of the crude hexagonal boron nitride was added, followed by stirring at 300 rpm for 15 hours. After the above acid washing, the acid was filtered and the powder was washed again with 300 times the amount of pure water with a resistivity of 1 MΩ cm at 25°C as the amount of crude hexagonal boron nitride added, and then dehydrated by suction filtration until the moisture content in the filtered powder was 50 mass% or less.
[0074] After washing with pure water, the obtained powder was dried under reduced pressure at 200°C for 15 hours under a pressure of 1 kPaA to obtain a white boron nitride powder. This boron nitride powder had many lumps.
[0075] The obtained boron nitride powder was placed in a carbon container (inner diameter 400 mm, inner height 50 mm) that was surface-coated with boron nitride, and cooled to a density of 0.20 g / cm 3 The mixture was packed to a height of 45 mm, and 10 of these were stacked in a graphite Tammann furnace with an internal volume of 1,000 L. The nitrogen gas flow rate into the furnace was 40 L (volume at 25°C) / min, the temperature was raised to 1500°C at 15°C / min, and the furnace was held at 1500°C for 4 hours to carry out a modification treatment. After cooling, the resulting modified boron nitride powder had few lumps. The carbon container had nitrogen flow paths between each stage so that nitrogen could flow above the powder layer.
[0076] The modified boron nitride powder thus obtained was subjected to the measurements (1) to (10) above. The production conditions and modification treatment conditions for the boron nitride powder are shown in Table 1, and the measurement results are shown in Table 3. In Table 1, the maximum temperature shown in the section on reduction-nitridation is the maximum temperature in the entire reduction-nitridation process, including the crystallization process after the reduction-nitridation reaction. This is also true for Tables 2 and 5 described below. In Tables 1 and 2, in the section on fluidization, "x" indicates that the powder to be modified was not fluidized, but was left stationary while an inert gas was passed through it. In Table 2, "o" indicates that the modification was performed in a fluidized bed.
[0077] In addition, the modified boron nitride powder was visually inspected for the occurrence of lumps and evaluated according to the following criteria, which are also shown in Table 3. (The same criteria are used in Table 6.) ◎: Fluffy and almost no lumps. 〇: Some lumps are observed, but it is fluffy. ×: Many lumps were observed, and the texture felt heavy.
[0078] <Examples 2 to 7, 11, Comparative Examples 1 to 6> Modified boron nitride powder was produced by changing the proportion of calcium carbonate in Example 1, the maximum temperature and maximum temperature holding time in crystallization after reduction nitridation, the powder packing density in the modification treatment (heat treatment), the type of inert gas, the flow rate of the inert gas, the treatment temperature, and the temperature holding time. The production conditions and modification treatment conditions of the boron nitride powder in the examples are shown in Table 1 or 2, and the measurement results are shown in Table 3 or 4. The production conditions and modification treatment conditions of the boron nitride powder in the comparative examples are shown in Table 5, and the measurement results are shown in Table 6.
[0079] <Example 8> In the same manner as in Example 1, crude hexagonal boron nitride powder was obtained. The resulting crude hexagonal boron nitride powder was then placed in a polyethylene container, and an aqueous hydrochloric acid solution (10% by weight HCl) was added in an amount 10 times the amount of the crude hexagonal boron nitride, followed by stirring at 300 rpm for 15 hours. After the acid washing, the acid was filtered, and the mixture was washed again with pure water having a resistivity of 1 MΩ·cm at 25°C in an amount 300 times the amount of the crude hexagonal boron nitride added, and then dehydrated by suction filtration until the moisture content in the filtered powder was 50 wt% or less.
[0080] After washing with pure water, the obtained powder was dried under reduced pressure at 200°C for 15 hours under a pressure of 1 kPaA to obtain a white boron nitride powder. The boron nitride powder had many lumps.
[0081] In order to determine the gas flow rate required to fluidize the boron nitride powder, an air permeability test was performed using a powder fluidity measuring device REVOLUTION manufactured by Mercury Scientific. The method of the air permeability test was the same as the dynamic fluidity test in (10) above, but differed in that the test was performed while supplying air from the bottom of a 160 mL split container, and the torque (mJ) applied to the impeller was measured while gradually increasing the air flow rate. The point at which the change in torque became small was the fluidization initiation flow rate (mm / sec), and the fluidization initiation flow rate of the boron nitride powder was 3.0 mm / sec.
[0082] Next, 600 g (approximately 5 L) of the boron nitride powder was filled into a carbon container (inner diameter 150 mm, inner height 600 mm) that was surface-coated with boron nitride. A gas supply port was provided at the bottom of the container, and gas was supplied into the container through a perforated plate, allowing the gas to escape to the top of the container.
[0083] The container filled with boron nitride powder was placed in a graphite Tammann furnace, and the nitrogen gas flow rate into the container was set to 0.6 L (volume at 25°C) / min, the temperature was raised to 1300°C at 15°C / min, and the container was held at 1300°C for 4 hours to carry out the modification treatment (nitrogen flow rate at 1300°C was 3.0 mm / sec). After cooling, the obtained modified boron nitride powder was fluffy and not lumpy. The manufacturing conditions and modification treatment conditions for the boron nitride powder are shown in Table 2, and the measurement results are shown in Table 4.
[0084] <Examples 9 and 10> Modified boron nitride powder was obtained by changing the type of inert gas, the flow rate of the inert gas, and the treatment temperature in the modification of Example 8 as shown in Table 2. The measurement results for the modified boron nitride powder are shown in Table 4.
[0085] [Table 1]
[0086] [Table 2]
[0087] [Table 3]
[0088] [Table 4]
[0089] [Table 5]
[0090] [Table 6]
[0091] [Cosmetics testing] Using the modified boron nitride powders obtained in the above Examples and Comparative Examples, powder foundations were prepared in the following blend ratios (however, for the modified boron nitride powders of Examples 6, 7, 10, and Comparative Example 5, the ratios of red iron oxide, yellow iron oxide, and black iron oxide were appropriately adjusted so that the color of the powder foundation would be equivalent to that when other white boron nitride powders were used).
[0092] Hexagonal boron nitride powder 20.0 mass% Mica 15.0% by mass Synthetic phlogopite 12.0% by mass Ethylhexyl methoxycinnamate 8.0% by mass (Vinyl Dimethicone / Methicone Silsesquioxane) Crosspolymer 8.0% by mass (Diphenyl Dimethicone / Vinyl Diphenyl Dimethicone / Silsesquioxane crosspolymer 8.0% by mass Nylon 12 3.0% by mass Silica 3.0% by mass Talc 3.0% by mass Acrylates crosspolymer 3.0% by mass Perfluorooctyltriethoxysilane 3.0% by mass Zinc oxide 3.0% by mass Polymethyl methacrylate polymer 3.0% by mass Silicone-treated iron oxide (red iron oxide) 1.0% by mass Silicone-treated yellow iron oxide 0.6% by mass Silicone-treated black iron oxide 0.4% by mass Silicone-treated titanium dioxide 6.0% by mass
[0093] The obtained powder foundation was applied to a cosmetic sponge and applied to the skin. In the visual inspection shown in Tables 3 and 4, those marked with ◎ gave a uniform finish with one application, but those marked with ○ and × in Table 6 gave uneven application with one application and required two to three applications to achieve a uniform finish. Furthermore, the powder foundations using the modified boron nitride powders of Examples 6, 7, and 10, and Comparative Example 5, which have a color close to human skin color, provided a more natural finish than those using other modified boron nitride powders with high whiteness.
Claims
1. A modified boron nitride powder characterized in that the voltage density measured by a triboelectric charging test is +10 V / g or more and +59 V / g or less, the whiteness (L value) is 90.0 or more, and the b value in the Lab color system is 4 or more and 14.1 or less.
2. 2. The modified boron nitride powder of claim 1, having an avalanche energy of 40 mJ / kg or less.
3. 2. The modified boron nitride powder according to claim 1, wherein the primary particles have an average major axis of 2 to 20 μm, an average thickness of 0.2 to 2.0 μm, and an average aspect ratio in the range of 5 to 20.
4. The modified boron nitride powder according to claim 1, which is used as a cosmetic compounding agent.
5. A method for modifying a negatively triboelectrically charged boron nitride powder, comprising heat-treating the powder at a temperature of 1700 to 2200°C in a rare gas flow until the voltage density measured by a triboelectric charging test is +10 V / g or more and +59 V / g or less, the whiteness (L value) is 90.0 or more, and the b value in the Lab color system is 4 or more and 14.1 or less.
6. 6. The method according to claim 5, wherein the negatively triboelectrically charged boron nitride powder is heat-treated while being fluidized under a flow of an inert gas.
Citation Information
Patent Citations
Ink for oxygen indicator and print obtained by using said ink
JP1986009466A
Hexagonal boron nitride powder, its manufacturing method and its use
JP2004035273A
High oil absorptive boron nitride powder excellent in heat release and cosmetics
JP2014094878A
Hexagonal boron nitride powder and cosmetics
JP2018108970A